2008
DOI: 10.1161/strokeaha.108.520817
|View full text |Cite
|
Sign up to set email alerts
|

Increased Stroke Risk Is Related to a Binge Drinking Habit

Abstract: Background and Purpose-Heavy alcohol consumption increases the risk for all strokes, whereas moderate regular alcohol consumption is associated with a lower risk for ischemic stroke. The purpose of this study was to evaluate the effect of different drinking patterns on stroke risk, independent of average alcohol intake. Methods-A prospective cohort study of 15 965 Finnish men and women age 25 to 64 years who participated in a national risk factor survey and had no history of stroke at baseline were followed up… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
95
2
4

Year Published

2008
2008
2019
2019

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 131 publications
(105 citation statements)
references
References 47 publications
(35 reference statements)
2
95
2
4
Order By: Relevance
“…A Swedish cohort study reported a higher risk of ischemic stroke among occasional heavy drinkers than among life-time abstainers (Romelsjo & Leifman, 1999). In the prospective cohort study binge drinking pattern was an independent risk factor for all strokes (Sundell et al, 2008). Comparing with non-binge drinkers, the hazard ratio for total stroke among binge drinkers was 1.85 (95% CI, 1.35 to 2.54) after adjusting for average alcohol consumption and other potential confounders.…”
Section: Y E Razvodovsky Grodno State Medical University Belarusmentioning
confidence: 92%
See 2 more Smart Citations
“…A Swedish cohort study reported a higher risk of ischemic stroke among occasional heavy drinkers than among life-time abstainers (Romelsjo & Leifman, 1999). In the prospective cohort study binge drinking pattern was an independent risk factor for all strokes (Sundell et al, 2008). Comparing with non-binge drinkers, the hazard ratio for total stroke among binge drinkers was 1.85 (95% CI, 1.35 to 2.54) after adjusting for average alcohol consumption and other potential confounders.…”
Section: Y E Razvodovsky Grodno State Medical University Belarusmentioning
confidence: 92%
“…There is evidence that pattern of drinking may have modifying influence on stroke risk independently of the amount of alcohol consumed (Sundell, Salomaa, Vartiainen, Poikolainen, & Laatikainen, 2008). Previous findings indicated an acute detrimental effect of binge drinking as a trigger of stroke.…”
Section: Y E Razvodovsky Grodno State Medical University Belarusmentioning
confidence: 99%
See 1 more Smart Citation
“…Hypertension ICH, whereas current smoking, diabetes, apolipoproteins and cardiac causes are associated with ischaemic stroke (O'Donnel et al 2016). (Seshadri & Wolf 2007) Decreased dietary vitamin D intake (Brøndum-Jacobsen et al 2013) Cardiovascular diseases (Ferro 2003, O'Donnel et al 2010 Ethnic background (Howard et al 2016) Diet (O'Donnel et al 2010) Cervical artery stenosis (Autret et al 1987) Gender (Wolf et al 1992, Traylor et al 2012 Excessive alcohol consumption (O'Donnel et al 2010, Sundell et al 2008 Diabetes (O'Donnel et al 2010) Genetics (Traylor et al 2012) Illicit drug use (Fonseca & Ferro 2013) Dyslipidemia (O'Donnel et al 2010) Inadequate physical activity (Hu et al 2005, O'Donnel et al 2010 Hormonal treatment (Farquhar et al 2009) Increased salt intake (Strazzullo et al 2009) Hypertension (Kannel et al 1970) Low level of training and low socioeconomic position (Cesaroni et al 2009) Migrane (Spector et al 2010) Obesity (Strazzullo et al 2010) Periodontal disease (Lafon et al 2014) Psychological stress (Huang et al 2015) Prothrombotic state (Ferro et al 2010) Smoking (Shinton & Beevers 1989) Snoring and sleep apnea (Dyken & Im 2009) …”
Section: Risk Factorsmentioning
confidence: 99%
“…In middle‐aged and older adults, binge drinking is associated with an increased risk of myocardial infarction, stroke, and hypertension 1, 2, 3, 4, 5. Binge drinking is also associated with an increased likelihood of developing prehypertension, previously defined as systolic blood pressure (SBP) between 120 and 140 mm Hg and diastolic blood pressure (DBP) between 70 and 90 mm Hg 6.…”
Section: Introductionmentioning
confidence: 99%